Plagiarism Reducing Aspects in Computer Supported Collaborative Learning Model - Sudmale, Sintija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Computer supported collaborative learning (CSCL) is a practical answer to futuristic e-Europe educational vision. Unsuccessfully organized collaborative work within teams of students, which ignores individual achievement and individual/ group responsibility balance, can lead to lack of motivation for personal involvement and promote plagiarism. The aim of this research is to theoretically analyze the plagiarism reducing aspects with computer supported collaborative learning.Applied study method - analyses of scientific sources. The main results are connected with the research of possibilities to solve the problem of plagiarism in education with modern cooperation methods.